Toponymics: semantics of stable lexical combinations in oral Kazakh tradition (Eurasian Journal of Philology Science and Education, 2022)
The article deals with the poetic creativity of the Kazakh people - zhyrau XV-XVIII centuries from the point of view of the inclusion in it of stable lexical combinations associated with the toponymic system of the ancient period. The richest works of the Kazakhs and other Turkic peoples that have saved to this day are the source of a comprehensive study and new philological searches built on the basis of the artistic and definitive system of epic works. The toponyms identified for analysis as a result of a continuous sample make it possible to judge the semantic diversity of stable lexical combinations, which testify to the uniqueness of the epic works of the Turkic peoples, as well as the special ability of the authors of zhyrau to convey hidden meanings and images, taking into account the intonation-sound nature of the worldview of the Turkic peoples, based on which lies the audioral and visual perception of the world. According to preliminary results, the authors selected about 40 lexical units in conjunction with the contexts of the statement, which are more stable combinations. A table has also been compiled in which the main key term is given, the frequency of its use, indicating the source of the fixation of the term, and poetic means, their types and functions in a specific contextual use of toponyms are selected. The article also proves the hypothesis of the project participants that the study of toponyms in zhyrau should be carried out taking into account their functional features and the rhythm of the text, since with the same size of the verse in the text there is a “stringing” of lexical units, through which the meaning of the whole work is revealed and the semantics is transformed depending on the degree of energy intensity.